Production flush of Agaricus blazei on Brazilian casing layers - Colauto, Nelson Barros; Silveira, Adriano Reis da [UNESP]; Eira, Augusto Ferreira da [UNESP]; Linde, Giani Andrea (Sociedade Brasileira de Microbiologia, 2011)
This study aimed to verify the biological efficiency and production flushes of Agaricus blazei strains on different casing layers during 90 cultivation days. Four casing layers were used: mixture of subsoil and charcoal (VCS), lime schist (LSC), São Paulo peat (SPP) and Santa Catarina peat (SCP); and two genetically distant A. blazei strains. The fungus was grown in composted substratum and, after total colonization, a pasteurized casing layer was added over the substratum, and fructification was induced. Mushrooms were picked up daily when the basidiocarp veil was stretched, but before the lamella were exposed. The biological efficiency (BE) was determined by the fresh basidiocarp mass divided by the substratum dry mass, expressed in percentage. The production flushes were also determined over time production. The BE and production flushes during 90 days were affected by the strains as well as by the casing layers. The ABL26 and LSC produced the best BE of 60.4%. Although VCS is the most used casing layer in Brazil, it is inferior to other casing layers, for all strains, throughout cultivation time. The strain, not the casing layer, is responsible for eventual variations of the average mushroom mass. In average, circa 50% of the mushroom production occurs around the first month, 30% in the second month, and 20% in third month. The casing layer water management depends on the casing layer type and the strain. Production flush responds better to water reposition, mainly with ABL26, and better porosity to LSC and SCP casing layers.
Keywords: production flush; Agaricus brasiliensis; casing layer; water management; Agaricus subrufescens